2021
DOI: 10.3389/fgene.2021.732002
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Disorders in Patients With Complex Phenotypes and Potential Complex Genetic Basis Involving Non-Coding Genes, and Double CNVs

Abstract: Neurodevelopmental disorders (NDDs) are a heterogeneous class of brain diseases, with a complex genetic basis estimated to account for up to 50% of cases. Nevertheless, genetic diagnostic yield is about 20%. Array-comparative genomic hybridization (array-CGH) is an established first-level diagnostic test able to detect pathogenic copy number variants (CNVs), however, most identified variants remain of uncertain significance (VUS). Failure of interpretation of VUSs may depend on various factors, including compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Transcriptomic analysis of RES complex genes in the mutant zebrafish identified the features of RES dependent introns [ 79 ]. Although no rare variants in BUD13 are reportedly causative in other genetic disorders, a copy number variant (CNV) investigation revealed a deletion in chromosome 11 spanning BUD13 in an individual with an NDD phenotype [ 80 ]. The same individual showed a deletion in chromosome 9 encompassing PTPRD , suggesting an additive effect in this patient [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Transcriptomic analysis of RES complex genes in the mutant zebrafish identified the features of RES dependent introns [ 79 ]. Although no rare variants in BUD13 are reportedly causative in other genetic disorders, a copy number variant (CNV) investigation revealed a deletion in chromosome 11 spanning BUD13 in an individual with an NDD phenotype [ 80 ]. The same individual showed a deletion in chromosome 9 encompassing PTPRD , suggesting an additive effect in this patient [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no rare variants in BUD13 are reportedly causative in other genetic disorders, a copy number variant (CNV) investigation revealed a deletion in chromosome 11 spanning BUD13 in an individual with an NDD phenotype [ 80 ]. The same individual showed a deletion in chromosome 9 encompassing PTPRD , suggesting an additive effect in this patient [ 80 ]. Additionally, the risk of developing a metabolic syndrome was associated with BUD13 through case-control studies [ 81 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significant allelic imbalance has been observed in up to 88% of genes in human tissues, potentially caused by genetic modifiers or stochastic factors ( Aguet et al, 2017 ), and has been identified as both tissue-specific and genome-wide in mouse models ( Pinter et al, 2015 ). Structural variants such as duplications that are in trans with a pathogenic LoF variant can alleviate the potential clinical phenotype when disease would be caused by haploinsufficiency, by providing an additional WT copy of a gene, thus resulting in a normal level of gene expression ( Servetti et al, 2021 ), as has been observed in DiGeorge syndrome ( Carelle-Calmels et al, 2009 ). Additional variants in the untranslated regions of mRNA can also affect the translational efficiency and gene expression can also vary widely across tissues, highlighting the importance of sequencing disease-relevant tissue in the interpretation of genetic variation ( Cummings et al, 2017 ; Mignone et al, 2002 ).…”
Section: Gene Expressionmentioning
confidence: 99%